Malnutrition-Sarcopenia Syndrome and its Associated Factors Among Older Adults. (17th December 2021) - Taani, Murad
Abstract: Malnutrition and sarcopenia are present in parallel in older adults and characterized by a combination of inadequate nutrient intake and decreased muscle mass, strength, and/or function. The presence of both conditions has been termed Malnutrition-Sarcopenia Syndrome (MSS) and is associated with negative health outcomes. The objective of this correlational study was to identify the prevalence and factors associated with the malnutrition-sarcopenia syndrome among older adults living in continuing care retirement communities. A convenience sample of 104 older adults living in CCRCs participated in this study. Muscle mass, strength, and function were measured using bioimpedance analysis, Jamar digital hand dynamometer, and the Short Physical Performance Battery test, respectively. Physical activity, sedentary time, and nutritional status were measured using ActiGraph GT3X and Mini Nutritional Assessment, respectively. Questionnaires were used to measure self-efficacy for exercise and goal congruence for physical activity and protein intake. Of the 104 participants, 37 (35.2%) had sarcopenia, 19 (18.1%) had malnutrition, and 14 (13.5 %) had MSS. Compared with those without MSS, older adults with MSS were more than two times more likely to have a sedentary lifestyle (Odd ratio, 2.028; 95% confidence interval, 2.012–2.044). Findings showed that sarcopenia, malnutrition, and MSS are prevalent in older adults living in continuing care retirement communities. Older adults should be screened and assessed for both malnutrition and sarcopenia. The results also suggest that decreasing the sedentary time could help in preventing MSS among older adults living in continuing care retirement communities.